The Dynamics of the Influence of Investor Sentiment on Capital Market Volatility in a Behavioral Finance Perspective - Dalimunthe, Fahmi Roy; Paranita, Ekayana Sangkasari; Suhara, Ade (Dinasti Publisher, 2025)
The dynamics of investor sentiment play a crucial role in the formation of capital market volatility, especially when psychological factors distort the supposedly rational decision-making process. In the perspective of behavioral finance, market behavior is influenced by collective emotions, cognitive biases, and information imperfections, which directly affect asset price movements and market stability. A secondary data-driven analysis from the period 2018 to 2023 of Indonesia's capital market indices indicates a significant correlation between fluctuations in investor sentiment and the level of market volatility. With the ARCH-GARCH model approach, it was identified that a surge in positive sentiment tends to increase volatility in the short term due to the overreaction effect, while the dominance of negative sentiment is associated with more prolonged selling pressure due to the influence of loss aversion and herding behavior. These findings reinforce the argument that markets are not entirely informationally efficient, but rather are heavily influenced by the collective perceptions and psychology of market participants. The implications of this study include the need to strengthen financial literacy based on investor psychology, reformulation of risk management strategies by market participants, and the development of policy instruments that are able to anticipate behavioral deviations from market rationality.